МОВНА ОСВІТА В УМОВАХ ЄВРОІНТЕГРАЦІЙНИХ ПРОЦЕСІВ (Педагогіка вищої та середньої школи, 2010)
The article deals with influence of integration and globalization processes on the role offoreign languages and methods of their studying in European countries.